2021
DOI: 10.1177/14034948211020599
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long-term physical activity interventions in communities: Scoping review in the Nordic countries

Abstract: Aims: Physical activity (PA) is an important part of maintaining good overall health. Currently, the number of insufficiently physically active adults and children is alarmingly high worldwide. To tackle the challenge, several interventions have been conducted, however, current knowledge on intervention effectiveness is still inconclusive. This scoping review aimed to summarize the effects of long-term PA interventions across all age groups in the Nordic countries. Methods: A scoping review was conducted by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(166 reference statements)
0
4
0
Order By: Relevance
“…It is unclear if PA interventions are dose-response dependent. A scoping review in communities in the Nordic countries found no additional increase in PA or fitness from long-term (≥12 months) interventions compared with interventions of less duration (Haverinen et al ., 2022 , Samdal et al ., 2017 ). In the present study, 83% of participants attended the HLC interventions for more than three months, therefore, it does not seem likely that additional intervention duration should affect the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if PA interventions are dose-response dependent. A scoping review in communities in the Nordic countries found no additional increase in PA or fitness from long-term (≥12 months) interventions compared with interventions of less duration (Haverinen et al ., 2022 , Samdal et al ., 2017 ). In the present study, 83% of participants attended the HLC interventions for more than three months, therefore, it does not seem likely that additional intervention duration should affect the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…To date, despite large evidence on the benefits of PA for people with BC, the extent to which PA programs could be effectively adopted, implemented and sustained remains unclear (16)(17)(18)(19)(20). Previous literature has shown mixed results over the long-term impact of interventions on PA practice (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…To date, despite large evidence on the benefits of PA for people with BC, the extent to which PA programs could be effectively adopted, implemented and sustained remains unclear (16)(17)(18)(19)(20). Previous literature has shown mixed results over the long-term impact of interventions on PA practice (16,17). Indeed, several programs have achieved limited success in improving PA among adults, particularly due to a lack of maintenance and sustainability of practice once the intervention ends (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…With a physical activity approach focused on health outcomes (i.e., meet the guidelines to avoid non-communicable disease), little attention is directed at why we move, and the motivational structures associated with this. Though there exist various approaches to increase physical activity, few long-term successes (limited to efficacy) can be demonstrated ( 3 , 4 ), and part of this failure may be due to a focus on instrumental valuation as opposed to intrinsic valuation of movement ( 5 ). Shifting away from the dehumanizing physical activity promotion strategies to support intrinsic valuation of movement ( 6 ), as exemplified in physical literacy through concurrent development of competence and psychological characteristics such as confidence and motivation ( 7 ), may be a way to support more sustainable behaviour change.…”
Section: Introductionmentioning
confidence: 99%